Images Of Islam’s Enemies Portrayed In the Arabic Poem Of Ka'ab Ibn Malik: A Representation-Based Analysis In The Prophetic Biography Context - Nurul Iman Mohamad Anuar Kamal; Mohamad Zulfazdlee Abul Hassan Ashari; Anwar Muttaqin; Ezad Azraai Jamsari; Md Nor Abdullah; Nursafira Lubis Safian (Ijaz Arabi Journal of Arabic Learning, 2026)
War poetry in the early Islamic era functioned as a historical record as well as a cultural instrument that helped shape, identity and define morality, while  framing the perception of an ‘enemy’. However, current research on Kaʿab ibn Malik’s poetry had focused largely on textual, stylistic or biographical aspects, with limited attention to how the enemy’s images are linguistically constructed and ideologically expressed in his poetry. This gap limits a deeper understanding of how early Islamic poetic discourse participated in the formation of collective memory and social boundaries. This study aimed to identify the various categories of enemy representation in Kaʿab’s war poetry, analyse the linguistic and rhetorical strategies used to construct these images, and evaluate their ideological functions in the Prophetic biography based on a socio-historical context. This qualitative study employed a textual analysis guided by Representation Theory and Enemy Image Theory. The findings reveal six dominant patterns, namely betrayal, cowardice, aggression, doctrinal threat, resistance to the prophetic mission, and moral disgrace. These categories interact to create a unified ideological narrative in which the Muslim community is elevated through moral legitimacy, while its opponents are severely limited through strategic othering. This study also revealed that Kaʿab ibn Malik’s poetry is a literary expression and a structured discourse that reinforces collective identity, moral cohesion and the early Muslim community’s worldview.